Results of scoping review do not support mild traumatic brain injury being associated with a high incidence of chronic cognitive impairment: Commentary on McInnes et al. 2017. - Grant L Iverson; Justin E Karr; Andrew J Gardner; Noah D Silverberg; Douglas P Terry (PLoS ONE)
A recently published review of 45 studies concluded that approximately half of individuals who sustain a single mild traumatic brain injury (MTBI) experience long-term cognitive impairment (McInnes et al. Mild Traumatic Brain Injury (mTBI) and chronic cognitive impairment: A scoping review. PLoS ONE 2017;12:e0174847). Stratified by age, they reported that 50% of children and 58% of adults showed some form of cognitive impairment. We contend that the McInnes et al. review used a definition of "cognitive impairment" that was idiosyncratic, not applicable to individual patients or subjects, inconsistent with how cognitive impairment is defined in clinical practice and research, and resulted in a large number of false positive cases of cognitive impairment. For example, if a study reported a statistically significant difference on a single cognitive test, the authors concluded that every subject with a MTBI in that study was cognitively impaired-an approach that cannot be justified statistically or psychometrically. The authors concluded that impairment was present in various cognitive domains, such as attention, memory, and executive functioning, but they did not analyze or report the results from any of these specific cognitive domains. Moreover, their analyses and conclusions regarding many published studies contradicted the interpretations provided by the original authors of those studies. We re-reviewed all 45 studies and extracted the main conclusions from each. We conclude that a single MTBI is not associated with a high incidence of chronic cognitive impairment.